Barriers Preventing to Reap the Benefits of E-commerce in Libya Prior and During COVID-19 Pandemic - Ihnissi, Ragab; Klaib, Alhadi (Journal of Pure & Applied Sciences, 2021)
Abstract: In Libya, there are a various barrier to developing e-commerce, and the COVID-19 pandemic has emphasised the importance of overcoming these hurdles in the shortest possible timeframe. This paper stems from a review of the studies which have focussed on the obstacles which preclude Libya reaping the benefits of e-commerce, at a time when many businesses are moving online, as a result of the lockdown introduced in response to COVID-19. This study has discussed and inspected the problems facing Libyan e-commerce. As a result of these problems, e-commerce has not taken hold in Libya or brought the country its considerable economic advantages. This paper suggests a range of recommendations which will contribute to adopt e-commerce in Libya and advance its popularity, among individuals, organisations and the government institutions, so that Libyan society can begin, and continue, to benefit from e-commerce.